The theoretical debate around heritage in relation to land use planning, rural space and tourism. Heritage as a concept, approach, process and attitude - Torres, César (2023)
The study of heritage requires new conceptual approaches that contribute to its current theoretical debate, in order to re-nourish the knowledge of different disciplines that address it. In between, richer and more complex crossovers are generated. This article presents the positions of different authors and submits them, especially, to the discussions on rural space, tourism and the logics of land use planning. As axes, work on heritage as a concept, approach, process and attitude is proposed. The conclusions will reveal that it is necessary to expand certain conceptual categories to better cover the heritage of rural areas, as well as a need to rethink tourism in that environment.